Fine Motor Stimulation Assisted by Bamboo Flute as a Learning Media for Mentally Disabled Students at Sunan Kudus Special Needs School - Margareta, Paulin; Muna, Fauzul; Wijayanto, Wasis (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2025)
Introduction/Main Objectives: The development of fine motor skills in mentally disabled students is still a challenge in learning in special schools (SLB). This study aims to analyze the application of bamboo flute media in learning activities to stimulate the fine motor skills of students with disabilities at SLB Sunan Kudus. Research Methods: This research used a qualitative approach of the case study type, with the subject of the skills teacher and five middle-level mentally disabled students. Data collection techniques were conducted through in-depth interviews and direct observation, while data analysis used thematic techniques with triangulation of techniques and sources. Finding/Results: The results showed that the use of bamboo flute media was able to improve finger coordination, motor accuracy, and student concentration during the learning process. The teacher also said that the bamboo flute is an interesting and easy-to-use media for students, although adaptation is needed in the early stages of use. This study has limitations in the number of subjects and a single school context, so it is recommended that future studies involve more participants and develop other traditional media variations that are suitable for the characteristics of students with special needs.